Analisis Tindak Tutur Representatif dalam Daftar Putar Video “Tips dan Edukasi” pada Kanal YouTube Zahid Ibrahim - Hening Jati Melani; Sabrina Fadilatul Khoiroh; Anggun Rizka Ramadania; Sakna Cahyani; Leyvisca Kristi Nugroho; Muhamad Syafiq Asyam; Asep Purwo Yudi Utomo; Arum Yuliya Lestari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Language is one of the tools used for communication. Speech acts employ language as a form of complex communication that considers the context, the speaker’s intent, and the expected reactions to understand the meaning and purpose of each utterance. This research describes the analysis of representative speech acts in the "Tips and Education" video playlist on Zahid Ibrahim's YouTube channel. The research method employed is descriptive qualitative analysis. The results of the study include representative speech acts such as: (1) representative speech acts of explaining, (2) representative speech acts of stating, (3) representative speech acts of informing, (4) representative speech acts of mentioning, (5) representative speech acts of suggesting, (6) representative speech acts of acknowledging, (7) representative speech acts of providing examples, and (8) representative speech acts of speculating. This research is expected to enhance readers’ knowledge in the field of pragmatics, particularly regarding representative speech acts, and can serve as a tool for developing speaking skills to clarify the intended meaning in communication.